Analisis Yuridis terhadap Penyelesaian Sengketa Sertipikat Ganda Hak Atas Tanah di Indonesia - Herlina (Institut Agama Islam Sunan Giri Ponorogo, 2026)
Dual certificate disputes are one of the complex problems in agrarian law in Indonesia that have an impact on legal uncertainty and material losses for the community. This study aims to analyze the legal construction of the causes of the issuance of double certificates and the dispute resolution mechanism, both administratively and judicially. The research method used is normative juridical with legislative, conceptual, and case approaches. Data were collected through literature studies from primary, secondary, and tertiary legal materials, which were analyzed qualitatively and prescriptively. The results of the study showed that the issuance of double certificates was caused by administrative defects, overlapping juridical and physical data, and land mafia practices. Administrative dispute resolution is carried out through a certificate cancellation mechanism by the Minister of ATR/Head of BPN based on stronger proof of ownership and good faith. Meanwhile, judicial settlement faces the dilemma of absolute competence between the District Court and the State Administrative Court (PTUN). Based on the Supreme Court Circular Letter (SEMA) Number 3 of 2010, disputes involving civil rights must be resolved in the general court, even though the object of the dispute is in the form of state administrative products. Harmonization between administrative law and civil law is very necessary to realize fair legal certainty.